ADMITTANCE CEREMONIES AND EMBASSY RELATIONS DURING THE PERIOD OF ASHTARKHANIDS (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzes the reception ceremonies and embassy relations during the administration of Ashtarkhanids with the help of materials from historical sources and information from foreign literature.